Post-partum Utero-ovarian Artery Rupture in Mare - Pazinato, Fernanda Maria; Curcio, Bruna da Rosa; Oliveira, Laura Corrêa; Santos, Alice Corrêa; Vieira, Patrícia Soares; Vargas, Sérgio Farias; Nogueira, Carlos Eduardo Wayne (Acta Scientiae Veterinariae, 2016)
Background: Arterial rupture associated with pregnancy is an important cause of fatal hemorrhage in pregnant mares, regardless breeds and age. Such hemorrhagic events lead to blood loss into the abdomen, broad ligament and uterus and the broad ligament hematoma occurs as a consequence of arterial rupture. Although the rupture of the uterine artery is commonly caused by hemorrhage, there are few studies regarding this condition. Therefore, the aim of this study was to describe a case of rupture of the utero-ovarian artery, with broad ligament hematoma and intramural uterine hematoma in a Thoroughbred mare, emphasizing the predisposing factors and the diagnosis process. Case: A 13-year-old Thoroughbred mare, with nine parturition, was attended with abdominal pain after foaling. The mare had an eutocic delivery, however the foal was a big one to the race, with high of 1,02 m and weight of 68 kg. The animal arrived at the Veterinary Clinical Hospital 48 h after delivery, with abdominal pain, pale mucous membranes, heart rate slightly increased. The trans-rectal palpation revealed the presence of a solid mass in the left horn region, and it was painful to the touch. The ultrasonography evaluation of the mass showed a heterogeneous texture with a hypoechoic central area, which reinforced the clinical suspicion of a hematoma in the broad ligament and a uterine intramural hematoma. The animal did not respond to analgesic therapy, which resulted in shock and consequently death. Necropsy revealed free blood in the abdominal cavity and the uterine wall with swollen hematoma extended to the left broad ligament. It also showed the presence of a hematoma along the uterine wall, from the uterine body region to the ovarian insertion. Histological evaluation did not show significant changes in the arterial wall, and it revealed the formation of intramural hematoma thorough all extension of the left uterine horn, confirming the suspicion of rupture in the utero-ovarian artery and hematoma on the broad ligament and uterine intramural hematoma in the left horn. Discussion: Rupture of uterine arteries can occur at any age, although it is often observe in old mares, possibly because of the vascular degenerative features observed in these animals. In addition, multiparous mares are more prone to it because multiple births can favour damages in vascular system. The clinical assessment showed characteristics compatible with postpartum hemorrhage. A thorough trans-rectal evaluation revealed a mass in the left horn. The ultrasonography evaluation from the mass showed echogenic characteristics consistent with those described for broad ligament hematoma and uterine intramural hematoma in the left horn. The clinical suspicion, rupture of the uterine artery, with formation of a hematoma in the broad ligament and uterine intramural hematoma, was based upon the history, clinical signs and laboratory tests, especially the characteristics revealed by the ultrasound from the mass in left horn. Necropsy showed the rupture of the utero-ovarian artery. Lesions are usually observed on the right uterine artery due to the displacement of the uterus to the left abdominal wall by the cecum, which results in an increased tension on the right broad ligament. However, in this case the rupture was associated to the gravid horn. The rupture of the utero-ovarian artery is a major cause of hemorrhage in the postpartum and this can form a hematoma in the broad ligament and uterine intramural hematoma. In conclusion, the mare from this study showed as the predisposing factors the age and the number of parturition. Clinical sings are very similar to others abdominal pain conditions, being the exams essential to diagnosis, especially ultrasonography. Rupture of the utero-ovarian artery is an emergency with unfavorable prognosis. Keywords: artery, utero-ovarian, mare, hemorrhage.